Mobile Application Development Using Semantic Mapping In Learning Vocabulary Arabic For Spesific Purposes (ASP)/ Pengembangan Aplikasi Mobile Dengan Semantic Mapping Dalam Pembelajaran Kosakata Arabic For Spesific Purposes (ASP) - Nasrullah, Muhammad; Degeng, I Nyoman Sudana; Murtadho, Nurul; Ulfa, Saida; Nugrawiyati, Jepri (Ijaz Arabi Journal of Arabic Learning, 2024)
The development of an online mobile application designed with semantic mapping flow for vocabulary learning in the context of Arabic for Specific Purposes (ASP) is accessible anytime and anywhere. It facilitates searching and learning vocabulary terms related to research methods for students majoring in Arabic Language Education (PBA) writing their theses. This research falls under the Research & Development (R&D) model, specifically the ADDIE model. Data analysis techniques involve descriptive statistical analysis. This study aims to develop an online mobile application for learning research method vocabulary in the context of ASP in higher education. The results indicate that assessments from media and content experts regarding the online mobile application received an average score of 4.54. This score suggests that the mobile application with semantic mapping flow is a suitable and effective tool for learning vocabulary in the context of ASP, despite minor revisions based on expert feedback. Feedback from 22 PBA students using the application after conducting an effectiveness test using the N-Gain test revealed that 86% of students considered the product very effective. In contrast, the remaining 14% categorized it as less effective. This is supported by an average pre-test score of 74.4 and an average post-test score of 96.8, resulting in an N-Gain value of 86%, indicating a high level of effectiveness for the developed product.